ChemInform Abstract: 2‐Iodoisatogens: Versatile Intermediates for the Synthesis of Nitrogen Heterocycles. Issue 23 (June 2015) - Maduli, Elvis J. M.; Edeson, Steven J.; Swanson, Stephen; Procopiou, Panayiotis A.; Harrity, Joseph P. A.
Abstract The Cu(I)‐promoted cyclization of 2‐nitrophenylhaloacetylenes to 2‐iodoisatogens is described.